2020
DOI: 10.3892/ol.2020.11682
|View full text |Cite
|
Sign up to set email alerts
|

Serum microRNA‑592 serves as a novel potential biomarker for early diagnosis of colorectal cancer

Abstract: Colorectal cancer (CRC) is the second leading cause of cancer-associated mortality worldwide. Currently, available diagnostic biomarkers are neither sensitive nor specific. Thus, the present study aimed to identify novel circulating microRNAs (miRNAs) as biomarkers for the early diagnosis of CRC. All samples were provided by The Second Affiliated Hospital of Nanjing Medical University (Nanjing, China). Analysis of the GSE108153 and GSE55139 datasets, downloaded from the Gene Expression Omnibus (GEO) database w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…10−12 In addition to clinical diagnostic methods, several scholars have made preliminary explorations of diagnostic markers for CAA. Respiratory volatile organic compounds, 13 serum autoantibodies, 14 serum M2-pyruvate kinase, 15 fecal miRNA-135b, 16 plasma matrix metalloproteinase, 17 serum circulating tumor DNA (ctDNA), 18 , 19 and miRNA-21/592 20 , 21 are still lack of high sensitivity or specificity for the CAA diagnosis. Furthermore, although the levels of nine amino acids in CAA tissue are significantly different from those in normal intestinal mucosa, reliance on colonoscopy and invasive tissue samples is not suitable for its early screening.…”
Section: Introductionmentioning
confidence: 99%
“…10−12 In addition to clinical diagnostic methods, several scholars have made preliminary explorations of diagnostic markers for CAA. Respiratory volatile organic compounds, 13 serum autoantibodies, 14 serum M2-pyruvate kinase, 15 fecal miRNA-135b, 16 plasma matrix metalloproteinase, 17 serum circulating tumor DNA (ctDNA), 18 , 19 and miRNA-21/592 20 , 21 are still lack of high sensitivity or specificity for the CAA diagnosis. Furthermore, although the levels of nine amino acids in CAA tissue are significantly different from those in normal intestinal mucosa, reliance on colonoscopy and invasive tissue samples is not suitable for its early screening.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing the remaining potential miRNAs, according to the present bioinformatics analysis (miR-93-5p, miR-23c, miR-210-3p, miR-221-3p, and miR-592), all were suggested with important roles in PC screening [61], aggressiveness [8,62,63], and recurrence [7,18,64], or even new etiological values [65] were suggested. These miRNAs have also been highlighted with carcinogenic effects in other tumors, such as endometrial [66,67], osteosarcoma [68], hepatocellular [69], renal [17,70], or colorectal [71], among others [72][73][74]. According to our experimental analysis, miR-210-3p, miR-23c, and miR-592 were suggested as aggressiveness biomarkers in PC and miR-93-5p, miR-130b, and miR-141 were suggested as diagnostic biomarkers for this tumor.…”
Section: Discussionmentioning
confidence: 62%
“…miR-217 in osteosarcoma is higher than the tissues near osteosarcoma, and can affect the prognosis of patients. The expression level of miR-217 is related to the pathological grade and clinical stage of the tumour (24). The expression levels of miR-592 and miR-217-3p are respectively related to family genetic history, tumour bias, optic nerve infiltration, lymph node metastasis, and degree of differentiation in Rb patients, further suggesting that the levels of miR-592 and miR-217-3p are related to the clinical features of Rb patients.…”
Section: Discussionmentioning
confidence: 94%
“…More and more studies have shown that miRNA expression can change various cellular pathogenesis signals and may become a new biomarker for tumour diagnosis and a potential target for tumour treatment (21)(22)(23). It has been found that various tumours and cancer cells, e.g., prostate cancer and osteosarcoma, secrete miR-217, which can be used as a diagnostic marker for the early detection of tumours (24). Meanwhile, the presence of miR-592 in serum has been correlated with the early detection of colorectal cancer and glioblastoma (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%